2018
DOI: 10.1016/j.freeradbiomed.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

UVA-induced carbon-centred radicals in lightly pigmented cells detected using ESR spectroscopy

Abstract: Rachel (2018) UVA-induced carbon-centered radicals in lightly pigmented cells detected using ESR spectroscopy. Free Radical Biology and Medicine .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Recent EPR studies have also shown the photo-production of ROS from melanins in melanocytes and skin itself [51,52]. In Kassouf et al [51], the spin trapping of radicals produced via UVA irradiation of melanocytes and melanoma cells showed higher levels of spin trapped carbon-centred radicals in lightly pigmented cells than in darkly pigmented or even non-pigmented cells.…”
Section: Melanins and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent EPR studies have also shown the photo-production of ROS from melanins in melanocytes and skin itself [51,52]. In Kassouf et al [51], the spin trapping of radicals produced via UVA irradiation of melanocytes and melanoma cells showed higher levels of spin trapped carbon-centred radicals in lightly pigmented cells than in darkly pigmented or even non-pigmented cells.…”
Section: Melanins and Covid-19mentioning
confidence: 99%
“…Recent EPR studies have also shown the photo-production of ROS from melanins in melanocytes and skin itself [51,52]. In Kassouf et al [51], the spin trapping of radicals produced via UVA irradiation of melanocytes and melanoma cells showed higher levels of spin trapped carbon-centred radicals in lightly pigmented cells than in darkly pigmented or even non-pigmented cells. Albrecht et al [52] used EPR spin trapping to detect radicals directly in irradiated skin and found radical production when the skin was irradiated with either UV, visible, or even infra-red light.…”
Section: Melanins and Covid-19mentioning
confidence: 99%
“…generated in the process of nitric oxide synthesis, and these oxygen-centered radicals are grouped into reactive oxygen species (ROS) [ 39 , 45 ]. Ultraviolet-A (UV-A) irradiation can potentially generate carbon radicals (carbon-centered radicals, reactive carbon species (RCS)) and hydroxyl radicals and damage nucleic acids in the skin cells/low pigmented (low melanin) skin cells [ 53 ].…”
Section: Oxidants and Antioxidantsmentioning
confidence: 99%